Mid-term report: Precision zone ventilation design and control in pig housing - Zong, Chao (Technical Report Biological and Chemical Engineering, 2013)
This report contains introduction of the project of precision zone ventilation design and control in pig housing. The work progress including activities, courses, and manuscript was presented. There is also a plan for further work. The ventilation system in pig housing has significant influences on local thermal conditions, indoor air quality and emission to neighbouring atmosphere. Precision zone ventilation, consisting of direct air supply into the Animal Occupied Zone (AOZ) and precision exhaust ventilation from the source zone, may provide more efficient climate control and improved air quality compared with conventional ventilation system. Removing the heat and pollutants directly at the sources will reduce the need for ventilation capacity, and result in reduced energy consumption and emission of ammonia and odours. Direct air supply into the AOZ will provide effective thermal control and better welfare for animals during warm weather, especially for a system with only diffuse ceiling inlets. Precision partial source zone ventilation directed at the manure pit, with only a part of the total ventilation capacity, will yield a high effectiveness of the air purification process. Cleaning only the partial exhaust air from the ventilated room space, the requirement on the airflow capacity of the cleaning unit will be reduced. Furthermore, it will reduce the spreading of airborne pathogens between pens. Research on this issue regarding experiments and mathematical modelling is essential. Besides, an optimization of precision zone ventilation related to location and design of the ventilation units, the characteristics of direct air supply to the AOZ and analysis of potential approaches will also need to be investigated. The objectives of this project is to develop the knowledge of precision zone ventilation in pig production buildings, aiming at achieving more effective ventilation and improving indoor air quality as well as reducing the required capacity of air cleaning devises.